Using quality improvement to close HIV prevention gaps and strengthen district health systems: Blantyre, Malawi's approach and early implementation - Allinder, Sara M.; Moses, Edward; Enock, Moses; Kawalazira, Gift; Nyirenda, Rose; Gonani, Andrew; Kamgwira, Yohane; Agins, Bruce; Birchard, Richard; Murungu, Joseph; Hoege, Deborah; Holmes, Charles B.; et al. (Frontiers in Reproductive Health, 2025)
Application of quality improvement (QI) methodology to HIV prevention is relatively nascent but has the potential to transform national and local programs. In Blantyre, Malawi, a unique government-led partnership known as the Blantyre Prevention Strategy (BPS) is applying QI as a core element of a cohesive sub-national HIV prevention system. BPS launched a QI collaborative (QIC) in early 2021—the first of its kind dedicated to HIV prevention within a health system context—focused on scale-up of pre-exposure prophylaxis (PrEP) to prevent HIV. Known as PrEPUp!, the QIC included 23 participating facilities—representing the public and private sectors, drop-in centers for key populations, and a tertiary education clinic—and has become the major platform for facility teams to exchange knowledge and share progress. Based on the implementation of QI activities, interventions identified for testing resulted in health center system modifications that promotes increased uptake of PrEP. In addition, knowledge generated through the QIC informs other stakeholders, including implementing partners funded by the U.S. President's Emergency Plan for AIDS Relief (PEPFAR), and improves coordination and mentoring executed by the Blantyre District Health Office (DHO). In a departure from traditional QI, BPS has engaged community labs that generate insights from clients and other influential stakeholders about demand and service access barriers and has connected those labs with facilities through learning sessions. This approach has been widely lauded locally in Malawi and is being adapted in Lilongwe District to underpin implementation science for injectable PrEP.